Polystyrene plastic for SMT (Surface Mount Technology) carrier tape and preparation method of polystyrene plastic
By introducing end alkenyl polysiloxane into polystyrene and heat treatment, combining anti-aging agent to modify polycarbonate and silane coupling agent to modify nanotitanium dioxide, the poor durability and aging problems of polystyrene at high temperatures are solved. , achieved significant improvements in the heat resistance, mechanical and anti-aging properties of polystyrene plastics.
Patent Information
- Application Number
- CN202411786678.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polystyrene has poor durability at high temperatures and is prone to softening. It also causes devitrification and cracks in sunlight, affecting its service life. It is difficult for existing modification methods to take into account both mechanical properties and anti-aging properties.
Modify polystyrene by introducing end alkenyl polysiloxane and performing heat treatment; modifying polystyrene with anti-aging agent; modifying nanotitanium dioxide with silane coupling agent, and adjusting heat treatment conditions and Material ratio improves the heat resistance, mechanical and anti-aging properties of plastics.
It significantly improves the heat resistance, tensile properties, mechanical impact properties and anti-aging capabilities of polystyrene, extends the service life of SMT carrier tape, and improves its comprehensive performance under different application conditions.
Smart Images

Figure CN119432094A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polystyrene materials, in particular to a polystyrene plastic for SMT carrier tape and a preparation method thereof. Background Art
[0002] SMT (Surface Mount Technology) carrier tape is a plastic tape used for packaging and transporting electronic components, and is widely used in the field of electronic manufacturing. SMT carrier tape has the advantages of high density, small size of electronic products, and light weight. The volume and weight of SMT carrier chip components are only about 1 / 10 of traditional plug-in components. After adopting SMT, the volume of electronic products is reduced by 40%-60%, and the weight is reduced by 60%-80%. It has the advantages of high reliability, strong shock resistance, easy automation, and improved production efficiency. SMT carrier tape is usually made of a variety of plastic materials. Compared with paper carrier tape, plastic carrier tape has better mechanical strength and moisture resistance, and is suitable for thicker chip components. SMT carrier tape is widely used in the packaging of electronic components such as IC, resistors, capacitors, connectors, etc., so different characteristics are achieved by modifying the carrier tape plastic to meet different application requirements.
[0003] Polystyrene is a polymer formed by free radical addition polymerization of polystyrene monomers. It is usually an amorphous random polymer with excellent thermal insulation, insulation and transparency. Its long-term use temperature is 0-70°C. It is one of the five commonly used engineering plastics. Due to its good processability and high hardness and rigidity, it is widely used in SMT carriers.
[0004] However, polystyrene has poor high temperature resistance, with a softening temperature of 80°C. It will become softer above 80°C and can usually only be used at low temperatures. Secondly, the presence of olefin bonds makes the plastic have poor aging resistance. If left in sunlight for a long time, it will gradually turn yellow, lose transparency and crack, which will affect the service life. It has poor toughness and strong brittleness, and is prone to cracking during application, affecting the normal use of the carrier. Therefore, it is necessary to modify polystyrene to enhance its high temperature resistance, aging resistance and comprehensive mechanical properties to meet the different application conditions of SMT carriers.
[0005] Patent CN101475721B reports antistatic plastics for SMT carriers, and preparation methods and applications thereof. Polystyrene is modified by conductive carbon black, polystyrene, styrene butadiene copolymer elasticity, toughening agents, antioxidants and coupling agents to improve the antistatic ability and mechanical properties of the plastic. However, the anti-aging ability is poor, and long-term use reduces the overall mechanical properties of the SMT carrier and reduces the service life.
[0006] In the prior art, since SMT carriers need to meet the packaging requirements of various electronic components, the wear resistance of plastic carriers decreases under electromagnetic influence, and their service life is shortened. In the prior art, the mechanical strength is improved by modifying the carrier plastic. However, it is not possible to improve both the mechanical properties and the anti-aging properties at the same time. Under long-term use conditions, insufficient anti-aging ability leads to a shortened service life of the SMT carrier, and poor mechanical properties further limit the application of the carrier.
[0007] Therefore, a polystyrene plastic for SMT carrier tape and a preparation method thereof are proposed. Summary of the invention
[0008] The invention aims to provide a polystyrene plastic for SMT carrier tape and a preparation method thereof. The invention comprises the following steps: introducing terminal olefin polysiloxane into a main chain of polystyrene and obtaining modified polystyrene after heat treatment; modifying polycarbonate by using an antioxidant to obtain modified polycarbonate; modifying nano titanium dioxide by using a silane coupling agent to obtain modified nano titanium dioxide; and preparing the polystyrene plastic for SMT carrier tape by melt extruding the modified polystyrene, the modified polycarbonate, the modified nano titanium dioxide and an auxiliary agent; improving the heat resistance of polystyrene by controlling the temperature and time of heat treatment and adjusting the cooling rate; improving the tensile property by adjusting the mass fraction ratio of polystyrene to terminal olefin polysiloxane; improving the mechanical impact property by adjusting the dosage of modified polyethylene and modified polycarbonate and adding a toughening agent; improving the anti-aging ability by controlling the dosage of modified polycarbonate and the dosage of the antioxidant; and improving the wear resistance of the plastic by using KH-570 as a silane coupling agent and controlling the dosage of modified titanium dioxide.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] The present invention provides a method for preparing a polystyrene plastic for an SMT carrier tape, wherein the preparation of the polystyrene plastic comprises the following steps:
[0011] 40-80 parts of modified polystyrene, 20-60 parts of modified polycarbonate and 10-25 parts of modified inorganic particles are vacuum dried to obtain a dried material; the dried material is added into a continuous mixer, 5-15 parts of a toughening agent, 3 parts of a lubricant and 5 parts of an antioxidant are added under stirring conditions, the temperature is raised to 220° C., and the mixture is stirred and mixed for 30 minutes to obtain a rubber compound; the rubber compound is melt-extruded in a twin-screw extruder, plasticized and granulated to obtain the polystyrene plastic;
[0012] Polymerizing polystyrene with terminal olefinic polysiloxane to obtain a polystyrene precursor; and subjecting the polystyrene precursor to heat treatment to obtain the modified polystyrene;
[0013] The modified polycarbonate is prepared by subjecting diphenyl carbonate, bisphenol A and an antioxidant to transesterification under the action of sodium hydroxide and condensation polymerization;
[0014] Modifying the inorganic particles with a silane coupling agent at 60° C. to obtain the modified inorganic particles;
[0015] The lubricant is selected from calcium carbonate complex; the antioxidant is selected from antioxidant 1010.
[0016] Preferably, the calcium carbonate composite is a mixture of calcium carbonate with particle sizes of 5-8 microns and 0.1 microns; the mixture is mixed in a weight ratio of 1:4.
[0017] Preferably, the preparation of the modified polystyrene precursor comprises the following steps:
[0018] Add terminal hydroxyl polysiloxane and tert-butyl hydroquinone into a flask, dissolve in dichloromethane, and stir to obtain a mixed solution; add acryloyl chloride and triethylamine to the mixed solution, heat to 40°C, and react for 3 hours to obtain terminal olefin polysiloxane; add dibutyltin dilaurate to the terminal olefin polysiloxane, stir to react, and obtain a reaction liquid; add the polystyrene to the reaction liquid, and react at 80°C for 1 hour to obtain a reaction system; cool the reaction system, rotary evaporate, and dry to obtain a modified polystyrene precursor; wherein the mass ratio of polystyrene to terminal olefin polysiloxane is 1:5-15.
[0019] Preferably, the preparation of the modified polystyrene comprises the following steps:
[0020] The modified polystyrene precursor is added into a reaction kettle, the temperature is raised to 100-200°C, and the temperature is kept for 30-90 minutes to obtain a melt; the melt is cooled at a cooling rate of 5-20°C / min to obtain a cooled product; the cooled product is rinsed and dried to obtain the modified polystyrene.
[0021] Preferably, the toughening agent is selected from one of polybutylene terephthalate, acrylonitrile-butadiene-styrene copolymer, styrene-butadiene-styrene block copolymer and ethylene-vinyl acetate copolymer.
[0022] Preferably, the preparation of the modified polycarbonate comprises the following steps:
[0023] Add diphenyl carbonate, bisphenol A and an antioxidant into a reaction bottle, add sodium hydroxide, and carry out ester exchange reaction at 200°C for 1 hour under a nitrogen atmosphere to obtain a mixed system; adjust the vacuum pressure of the mixed system to 30KPa, raise the temperature to 250°C and react for 30 minutes to obtain product one; reduce the pressure of product one to 5KPa, raise the temperature to 280°C and react for 30 minutes to obtain a polymer; dissolve the polymer in dichloromethane, add methanol to precipitate a precipitate; separate and centrifuge the precipitate, rinse with methanol, and vacuum dry at 80°C for 2 hours to obtain a modified polycarbonate.
[0024] Preferably, the mass ratio of diphenyl carbonate, bisphenol A and antioxidant is 10-30:15-45:1; the antioxidant is 2-(2,4-dihydroxyphenyl)-4,6-bis(2,4-xylyl)-1,3,5-triazine.
[0025] Preferably, the preparation of the modified inorganic particles comprises the following steps:
[0026] The inorganic particles were added to anhydrous ethanol, and ultrasonically vibrated for 30 minutes to obtain a suspension; the silane coupling agent was added to the anhydrous ethanol, and stirred for 30 minutes to obtain a modifier solution; the modifier solution was added to the suspension, and magnetic stirring was performed, and the modified reaction was carried out at 60° C. for 2 hours to obtain modified inorganic particles.
[0027] Preferably, the inorganic particles are selected from one of nano-titanium dioxide, nano-silicon dioxide, nano-graphene and nano-calcium carbonate.
[0028] Preferably, the silane coupling agent is selected from one of methylvinyldimethoxysilane, vinyltriisopropoxysilane and methacryloxypropyltrimethoxysilane; and the mass ratio of the inorganic particles to the silane coupling agent is 3-10:1.
[0029] The present invention also provides a polystyrene plastic for SMT carrier tape prepared by the method of claim 1, wherein the polystyrene plastic comprises modified polystyrene, modified polycarbonate, modified inorganic particles, a toughening agent, a calcium carbonate complex and an antioxidant 1010.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The present invention modifies polystyrene by terminal olefin polysiloxane and obtains modified polyethylene by heat treatment. High temperature is used to enhance the mobility of molecular chains, so that the chain segments are arranged into an orderly crystal structure, the crystallinity is increased, and the heat resistance of polystyrene is improved. By controlling the heat treatment temperature and time, the heat resistance of the obtained modified polystyrene is improved.
[0032] 2. The modified polystyrene obtained by the present invention through terminal olefinic polysiloxane is melt-extruded with modified polycarbonate. The flexible Si-O bond can disperse the external force under the action of external force, so that the plastic is evenly stressed. At the same time, the modified polycarbonate can form intermolecular hydrogen bonds with the polysiloxane, further improving the mechanical properties of the plastic. The tensile properties of the obtained polystyrene plastic are improved, and the mechanical strength of the SMT carrier is improved.
[0033] 3. The present invention improves the compatibility of modified polystyrene and modified polycarbonate by using ABS, and utilizes the acrylonitrile group in ABS to bond with the polar group in the modified polycarbonate, while the styrene chain segment and the modified polystyrene undergo graft copolymerization, thereby improving the compatibility and the impact performance of the plastic; by changing the type and amount of the toughening agent, the impact strength of the prepared polystyrene plastic is significantly improved, and the mechanical strength of the SMT carrier is improved.
[0034] 4. The present invention uses an antioxidant to modify polycarbonate, and the antioxidant is introduced into the main chain structure of the polycarbonate, thereby introducing an organic substance that resists ultraviolet shielding, thereby improving the anti-aging performance of the plastic, and solving the problem of poor compatibility between the polar group of the antioxidant and the modified styrene. By adjusting the amount of modified polycarbonate and the amount of antioxidant, the anti-aging ability of the prepared polystyrene plastic is significantly improved, thereby increasing the service life of the SMT carrier.
[0035] 5. The present invention uses inorganic particles modified by silane coupling agent as reinforcing fillers, uses modified nanoparticles to form physical crosslinks with polymers, and transmits stress to other molecular chains through crosslinked particles, so that the stress distribution is uniform and the friction stress in the local area is reduced; by controlling the type and amount of silane coupling agent, the volume wear of the obtained polystyrene plastic is 0.82mm 3 , the wear resistance is improved, and the service life of the SMT carrier is increased. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The graphs of tensile strength and elongation at break of Examples 17-21 of the present invention are as follows;
[0037] Figure 2 This is a graph showing the change in tensile strength of Examples 41-45 of the present invention before and after aging treatment. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] The EVA described in the present invention is ethylene-vinyl acetate copolymer; the ABS described is acrylonitrile-butadiene-styrene copolymer; the SBS described is styrene-butadiene-styrene block copolymer; the PBT described is polybutylene terephthalate; and the KH-570 described is methacryloxypropyltrimethoxysilane.
[0040] See also Figure 1 to Figure 2 The present invention provides a polystyrene plastic for SMT carrier tape and a preparation method thereof, and the technical scheme is as follows:
[0041] Example 1
[0042] Preparation of modified polystyrene:
[0043] 1 mol of terminal hydroxyl polysiloxane and 0.01 mol of tert-butylhydroquinone are added into a flask, 2 ml of dichloromethane is slowly added, and the mixture is stirred for 30 min at room temperature to obtain a mixed solution; 1.5 mol of acryloyl chloride and 1 ml of triethylamine are slowly added into the mixed solution, and the addition is complete within 10 min, the mixture is heated to 40° C., and the mixture is reacted for 3 h to obtain terminal olefin polysiloxane; 1 part of dibutyltin dilaurate (1% by mass of polystyrene) is added into 10 parts of the terminal olefin polysiloxane, and the mixture is stirred and reacted for 1 h under heat preservation to obtain a reaction solution; 100 parts of polystyrene are added into the reaction solution, the mixture is heated to 80° C., and the reaction is stirred for 1 h to obtain a reaction system; the reaction system is cooled to room temperature, the solvent is removed by rotary evaporation, and the mixture is dried at 60° C. for 2 h to obtain a modified polystyrene precursor.
[0044] The modified polystyrene precursor is added into a reactor, the temperature is rapidly raised to 100°C, and the temperature is kept for 30 minutes to obtain a molten material; the reactor is cooled at a cooling rate of 5°C / min to obtain a cooled material; the cooled material is rinsed with methanol and deionized water respectively, and vacuum dried at 80°C for 2 hours to obtain the modified polystyrene.
[0045] Diphenyl carbonate, bisphenol A, and 2-(2,4-dihydroxyphenyl)-4,6-bis(2,4-xylyl)-1,3,5-triazine are added to a reaction bottle at a molar ratio of 20:30:1, and sodium hydroxide is added. The mixture is heated to 200° C. under a nitrogen atmosphere, and the ester exchange reaction is carried out for 1 hour to obtain a mixed system, during which the by-product phenol is continuously distilled out of the mixed system; the vacuum pressure of the mixed system is adjusted to 30 KPa, the temperature is raised to 250° C., and the reaction is carried out for 30 minutes to obtain a product 1; the pressure of the product 1 is reduced to 5 KPa, the temperature is raised to 280° C., and the reaction is carried out for 30 minutes to obtain a polymer; the polymer is dissolved in dichloromethane, and methanol is added to precipitate a precipitate; the precipitate is separated and centrifuged, rinsed with methanol, and vacuum dried at 80° C. for 2 hours to obtain a modified polycarbonate.
[0046] Add 50 parts of nano-silica to 100 mL of anhydrous ethanol, and ultrasonically vibrate for 30 minutes to obtain a suspension; add 10 parts of KH-570 to 50 mL of anhydrous ethanol, and stir for 30 minutes to obtain a modifier solution; add the modifier hydrolyzate to the suspension, stir magnetically, and perform a modification reaction at 60° C. for 2 hours to obtain modified nano-silica.
[0047] 60 parts of the modified polystyrene, 40 parts of modified polycarbonate and 20 parts of modified nano-silicon dioxide are vacuum dried at 100°C for 4 hours to obtain a dried material; the dried material is added into a continuous mixer, 10 parts of ABS, 3 parts of calcium carbonate compound and 10105 parts of antioxidant are added under stirring conditions, the temperature is raised to 220°C, and stirring and mixing is performed at 800r / min for 30 minutes to obtain a rubber compound; the rubber compound is melt-extruded in a twin-screw extruder, plasticized and granulated to obtain the polystyrene plastic for SMT carrier tape.
[0048] Examples 2-15 refer to the preparation methods and parameter conditions of Example 1, with the differences shown in Table 1.
[0049] Table 1 Heat treatment parameters of Examples 1-15
[0050]
[0051]
[0052] Comparative Example 1 refers to the preparation method and parameter conditions of Example 1, except that terminal olefin polysiloxane-modified polystyrene is not added.
[0053] Comparative Example 2 refers to the preparation method and parameter conditions of Example 1, except that the modified polystyrene precursor is not subjected to a heat treatment process.
[0054] Comparative Example 3 refers to the preparation method and parameter conditions of Example 1, except that the polystyrene is not modified.
[0055] Example 16 Determination of heat deformation temperature
[0056] The modified polystyrene prepared in Examples 1-15 and Comparative Examples 1-3 was tested for the heat deformation temperature of plastics according to GB / T 1634.1-2019. The test results are shown in Table 1.
[0057] Table 2 Thermal deformation temperature test of Examples 1-15 and Comparative Examples 1-3
[0058]
[0059]
[0060] From the results in Table 2, it can be seen that in Comparative Examples 1-3, no modification treatment is performed, and the polystyrene obtained during the heat treatment process has a heat deformation temperature of 85°C. When this temperature is reached, the polystyrene plastic begins to undergo a glass transition, and the heat resistance is significantly reduced. After adding terminal olefin polydimethylsiloxane and heat treatment in Comparative Examples 1-2, the heat deformation temperature of the modified polystyrene is significantly improved, but it is still significantly reduced compared to Examples 1-15; From the results of Examples 1-9, it can be seen that with the increase of the heat treatment temperature and the heat treatment time, the heat deformation temperature of the modified polystyrene shows a trend of first increasing and then slowly decreasing. With the increase of temperature and time, the molecular chain of polystyrene begins to become active, the chain segments can be rearranged, and the crystallinity gradually increases. Due to the enhanced mobility of the molecular chain, the chain segments can be more effectively arranged into an ordered crystal structure. At the same time, the introduction of polysilicon makes the polystyrene molecules crystallize toward silicon atoms as a whole, further improving the crystallinity. However, with the continued increase of temperature and time, the treatment temperature approaches or exceeds the melting point, and the crystal structure of polystyrene The structure may begin to melt, resulting in a decrease in crystallinity. At this temperature, the polymer may enter an overheated state, and the movement of the molecular chain is too violent, which destroys the already formed crystal structure and causes a decrease in crystallinity. The results of Example 3 and Examples 10-13 show that with the increase of the cooling rate, the heat deformation temperature of the modified polystyrene shows a gradually decreasing trend, and the heat resistance gradually decreases. When the cooling rate is slow, the molecular chain is allowed to have more time to rearrange and crystallize with the silicon atoms, thereby increasing the crystallinity. With the increase of the cooling rate, the molten polystyrene can inhibit the movement of the molecular chain, reduce the chance of crystallization, and thus reduce the crystallinity. The results of Example 3 and Examples 14-15 show that with the addition of terminal olefin polysiloxane, the heat resistance of the modified polystyrene is significantly improved, but changing the portion ratio has little effect on the heat resistance of the modified polystyrene. It can be seen from the results of Table 2 that by controlling the temperature and time of the heat treatment and adjusting the cooling rate, the heat deformation temperature of the modified polystyrene obtained is 155°C, showing a significant improvement in heat resistance.
[0061] Embodiment 17
[0062] The preparation of modified polystyrene is as described in Example 3;
[0063] Diphenyl carbonate, bisphenol A, and 2-(2,4-dihydroxyphenyl)-4,6-bis(2,4-xylyl)-1,3,5-triazine are added to a reaction bottle at a molar ratio of 20:30:1, and sodium hydroxide is added. The mixture is heated to 200°C under a nitrogen atmosphere, and the ester exchange reaction is carried out for 1 hour to obtain a mixed system, during which the by-product phenol is continuously distilled out of the mixed system; the vacuum pressure of the mixed system is adjusted to 30KPa, the temperature is raised to 250°C, and the reaction is carried out for 30 minutes to obtain a product 1; the pressure of the product 1 is reduced to 5KPa, the temperature is raised to 280°C, and the reaction is carried out for 30 minutes to obtain a polymer; the polymer is dissolved in dichloromethane, and methanol is added to precipitate a precipitate; the precipitate is separated and centrifuged, rinsed with methanol, and vacuum dried at 80°C for 2 hours to obtain a modified polycarbonate.
[0064] Add 50 parts of nano-silica to 100 mL of anhydrous ethanol, and ultrasonically vibrate for 30 minutes to obtain a suspension; add 10 parts of KH-570 to 50 mL of anhydrous ethanol, and stir for 30 minutes to obtain a modifier solution; add the modifier hydrolyzate to the suspension, stir magnetically, and perform a modification reaction at 60° C. for 2 hours to obtain modified nano-silica.
[0065] 20 parts of the modified polystyrene, modified polycarbonate and modified nano-silica are vacuum dried at 100°C for 4 hours to obtain a dried material; the dried material is added into a continuous mixer, 10 parts of ABS, 3 parts of calcium carbonate compound and 10105 parts of antioxidant are added under stirring conditions, the temperature is raised to 220°C, and stirring and mixing is performed at 800r / min for 30 minutes to obtain a rubber compound; the rubber compound is melt-extruded in a twin-screw extruder, plasticized and granulated to obtain the polystyrene plastic for SMT carrier tape.
[0066] Examples 18-26 refer to the preparation method and parameter conditions of Example 17, and the differences are shown in Table 3.
[0067] Table 3 Component dosage of Examples 17-26
[0068]
[0069] Comparative Example 4 refers to the preparation method and parameter conditions of Example 17, except that terminal olefin polysiloxane-modified polystyrene is not added.
[0070] Comparative Example 5 refers to the preparation method and parameter conditions of Example 17, except that no modified polycarbonate is added.
[0071] Example 27 Tensile Strength Determination
[0072] The polystyrene plastics for SMT carrier tapes prepared in Examples 17-26 and Comparative Examples 4-5 were subjected to tensile strength and elongation at break tests using a Z100 electronic universal tester in accordance with GB / T1447-2005, with the tensile rate set at 20 mm / min. The test results are shown in Table 4. The tensile strength and elongation at break of Examples 17-21 vary as shown in Table 4. Figure 1 shown.
[0073] Table 4 Determination of tensile properties of Examples 17-26 and Comparative Examples 4-5
[0074] Example Tensile strength / MPa Elongation at break / % Embodiment 17 52.6 62.8 Embodiment 18 42.5 55.8 Embodiment 19 48.2 58.4 Embodiment 20 53.2 63.5 Embodiment 21 55.8 64.6 Embodiment 22 45.9 51.2 Embodiment 23 49.3 58.2 Embodiment 24 46.8 51.7 Embodiment 25 45.2 50.8 Embodiment 26 53.2 48.6 Comparative Example 4 20.3 8.5 Comparative Example 5 21.8 12.8
[0075] The results in Table 4 show that the tensile properties of the polystyrene material obtained by not adding terminal olefin polysiloxane to modify polystyrene in Comparative Example 4 are significantly lower than those in Examples 17-26, with a tensile strength of 20.3 MPa and an elongation at break of 8.5%. Since the polystyrene has not been modified by siloxane, the rigid group content of the benzene ring in the system is relatively high, which further reduces the elongation at break of the material; the tensile properties of the polystyrene plastic obtained by not adding modified polycarbonate in Comparative Example 5 are improved compared to Comparative Example 4, and the modified polycarbonate can form intermolecular hydrogen bonds with polysiloxane, further improving the mechanical properties of the material; Examples 17-21, Figure 1 The results show that with the increase of the mass fraction of terminal olefin polysiloxane, the tensile properties of polystyrene plastics show a significant improvement. Polysiloxane introduces flexible Si-O bonds. Under the action of external forces, the silicon-oxygen bonds can disperse the external forces, make the plastics evenly stressed, avoid the plastics from breaking, and improve the tensile strength. At the same time, long-chain polysiloxane can effectively reduce the intermolecular forces, and the applied stress can be dispersed in the straight chain. At the same time, the dispersed forces can improve the ductility of the plastics and the elongation at break. However, the continuous increase in the dosage reduces the compatibility of the plastic system and the overall mechanical properties decrease. The results of Example 17 and Examples 22-24 show that with the increase in the amount of modified polystyrene, the tensile strength of the material shows a gradually increasing trend. Potential, elongation at break shows a trend of first increasing and then decreasing. The dispersion degree of the long-chain siloxane bond introduced by the increase in dosage increases, and the effect of reducing the external force is obvious. With the further increase in dosage, the proportion of the rigid benzene ring group in the system increases, which affects the dispersion of the siloxane bond in the plastic. At the same time, the cyclic benzene ring structure effectively increases the strength of the plastic. However, due to the conjugation effect, the applied external force further enhances the intermolecular force in the structural system, resulting in a decrease in the elongation at break of the plastic. It can be seen from the results of Examples 17 and 25-26 that with the increase in the molecular weight of the terminal alkenyl polysiloxane, at the same dosage, the dispersion of the long siloxane chain of the terminal alkenyl polysiloxane in the plastic is better, showing significantly improved tensile properties. As shown in Table 4, Figure 1The results show that by controlling the amount of modified polystyrene and modified polycarbonate and adjusting the mass ratio of polystyrene to terminal olefinic polysiloxane, the tensile strength of the obtained polystyrene plastic is 52.6 MPa and the elongation at break is 62.8%, showing significantly improved tensile properties.
[0076] Examples 28-39 refer to the preparation method and parameter conditions of Example 17, and the differences are shown in Table 5.
[0077] Comparative Example 6 refers to the preparation method and parameter conditions of Example 17, except that no modified polycarbonate is added.
[0078] Comparative Example 7 refers to the preparation method and parameter conditions of Example 17, except that no toughening agent is added.
[0079] Example 40 Impact Strength Measurement
[0080] The polystyrene plastics prepared in Examples 28-39 and Comparative Examples 6-7 were subjected to impact strength tests using an impact tester (XJ-300A) according to the national standard GB / T 1843-2008. Before impact, the prepared test specimens were fixed stably with a fixture, and the pendulum of the impact tester was dropped at an angle of 150° during impact. The test results are shown in Table 5.
[0081] Table 5 Impact strength test of Examples 28-39 and Comparative Examples 6-7
[0082]
[0083] The results in Table 5 show that the impact strength of the polystyrene plastic prepared without adding modified polycarbonate in Comparative Example 6 is significantly lower than that of Examples 28-39. With the addition of modified polycarbonate, the rigid structure of the benzene ring in the polystyrene can cross-link with each other in the modified polycarbonate during the melting process, and the formed rigid network further improves the impact strength of the plastic; in Comparative Example 7, no toughening agent is added, resulting in a significant decrease in the compatibility between the modified polycarbonate and the modified polystyrene, and the impact strength shows a significant decrease; the results of Examples 28-31 show that with the change of the type of toughening agent, the impact strength of the polystyrene plastic changes significantly. The addition of the toughening agent can induce the formation of silver streaks and shear bands, consumes a lot of energy, and increases the impact strength of the plastic. The introduction of SBS and EVA reduces the compatibility between the modified polycarbonate and the modified polystyrene, and reduces the comprehensive mechanical properties of the plastic. The acrylonitrile group in ABS can bond with the polar group in the modified polycarbonate, and the styrene segment undergoes graft copolymerization with the modified polystyrene, showing significantly improved compatibility; Examples 28 and 31 show that the impact strength of the polystyrene plastic changes significantly with the change of the type of toughening agent. The addition of the toughening agent can induce the formation of silver streaks and shear bands, consumes a lot of energy, and increases the impact strength of the plastic. As shown in the results of Examples 32-35, with the increase of the amount of toughening agent, the impact strength of the plastic shows a trend of gradual increase. As the amount of toughening agent MXD6 increases, the impact strength of the plastic shows a trend of gradual increase. Since the modified polycarbonate is added to the plastic, the movement of the polystyrene molecular chain is hindered, and the impact strength of the plastic is improved; however, the introduction of excessive toughening agent forms a two-phase interface that is not conducive to stress conduction and is very likely to form a stress concentration point, thereby reducing the tensile properties of the plastic; As shown in the results of Examples 28 and 36-39, with the increase of the amount of toughening agent With the increase of the amount of modified polystyrene, the impact strength of the plastic shows a trend of first increasing and then decreasing. With the excessive increase of the amount of modified styrene, the toughening effect achieved by toughening can no longer maintain the compatibility balance between modified polycarbonate and modified polystyrene, resulting in a significant decrease in impact strength. From the results in Table 5, it can be seen that by using ABS as a toughening agent, controlling its amount, and adjusting the amount of modified polyethylene and modified polycarbonate, the impact strength of the prepared polystyrene plastic is 88.6MPa, showing a significantly improved mechanical impact resistance.
[0084] Examples 41-52 refer to the preparation method and parameter steps of Example 28, and the differences are shown in Table 6.
[0085] Comparative Example 8 refers to the preparation method and parameter steps of Example 28, except that no antioxidant is added to modify the polycarbonate.
[0086] Comparative Example 9 refers to the preparation method and parameter steps of Example 28, except that modified nano-titanium dioxide is not added.
[0087] Example 53 Anti-aging performance test
[0088] The polystyrene plastics prepared in Examples 41-52 and Comparative Examples 8-9 were placed in a UV aging test box for UV aging accelerated testing. The test temperature was 100°C, the light source was a 1000W high pressure mercury lamp, the distance between the sample and the light source was 20mm, and the irradiation time was 800h. The tensile strength of the composite material before and after irradiation was tested, and the strength retention rate was calculated. The changes in tensile strength of Examples 41-45 before and after aging treatment are shown in Figure 2. Figure 2 The test results are shown in Table 6.
[0089] Table 6 Anti-aging performance test of Examples 41-52 and Comparative Examples 8-9
[0090]
[0091]
[0092] The results in Table 6 show that the tensile strength retention rate of the polystyrene plastic prepared by adding polycarbonate without antioxidant modification in Comparative Example 8 is significantly lower than that of Examples 41-52, and the strength retention rate of the polystyrene plastic prepared by not adding modified nano titanium dioxide in Comparative Example 9 is significantly higher than that of Comparative Example 8, but still lower than that of Examples 41-52, indicating that the synergistic effect of the antioxidant and nano titanium dioxide makes the aging resistance of the polystyrene plastic reach the best; Examples 41-45, Figure 2 The results show that with the increase of the amount of antioxidant, the strength retention rate of the plastic shows a trend of gradually increasing. The antioxidant is used to modify the polycarbonate. Through the action of polar groups, the antioxidant is introduced into the main chain structure of the polycarbonate, and the organic matter with anti-ultraviolet shielding is introduced, which improves the anti-aging performance of the plastic. At the same time, the problem of poor compatibility between the polar groups of the antioxidant and modified styrene is solved. During the use of the plastic, the aging effect of free radical ions on the plastic is avoided. However, the excessive addition of antioxidants and the introduced polar groups further reduce the overall compatibility of the plastic and reduce the overall tensile strength of the material. Tensile strength; The results of Examples 43 and 46-49 show that with the increase in the amount of modified polycarbonate, the overall content of the antioxidant in the plastic increases, the dispersion improves, the adsorption capacity for free radical ions increases, and the strength retention rate is further improved. However, excessive addition leads to reduced compatibility and deterioration of mechanical properties; The results of Examples 43 and 50-52 show that with the change in the type of inorganic particles, the strength retention rate of the plastic changes significantly, and nano titanium dioxide has a significant ultraviolet light shielding effect, showing anti-aging properties synergistic with the antioxidant; Through Table 6, Figure 2 The results show that by controlling the amount of modified polycarbonate and the amount of antioxidant, the tensile strength retention rate of the prepared polystyrene plastic after irradiation at 100°C for 800 hours is 99.5%, and the anti-aging performance is significantly improved.
[0093] Embodiment 54
[0094] Add 50 parts of nano titanium dioxide into 100 mL of anhydrous ethanol, and ultrasonically vibrate for 30 minutes to obtain a suspension; add 10 parts of KH-570 into 50 mL of anhydrous ethanol, and stir for 30 minutes to obtain a modifier solution; add the modifier hydrolyzate into the suspension, stir magnetically, and perform a modification reaction at 60° C. for 2 hours to obtain modified nano silicon dioxide.
[0095] The preparation of polystyrene plastic for SMT carrier tape refers to Example 43.
[0096] Examples 55-62 refer to the preparation method and parameter conditions of Example 54, and the differences are shown in Table 7.
[0097] Comparative Example 10 refers to the preparation method and parameter conditions of Example 54, except that no modified titanium dioxide is added.
[0098] Comparative Example 11 refers to the preparation method and parameter conditions of Example 54, except that the titanium dioxide is not modified.
[0099] Comparative Example 12 refers to the preparation method and parameter conditions of Example 54, except that the lubricant is calcium carbonate.
[0100] Example 63 Wear resistance test
[0101] When the polystyrene plastics prepared in Examples 54-62 and Comparative Examples 10-12 were subjected to friction tests, the samples were installed above the counter-wear body and loaded with loads. The samples remained stationary, and the counter-wear body ring rotated at a certain speed. The calculation formula for volume wear (V) is as follows; the test results are shown in Table 7.
[0102] V=m1-m2 / ρ
[0103] Where m1 is the mass of the sample before the test, g; m2 is the mass of the sample after the test, g; ρ is the sample density, g / cm 3 .
[0104] Table 7 Wear resistance test of Examples 54-62 and Comparative Examples 10-12
[0105]
[0106] The results in Table 7 show that the volume wear of the polystyrene plastics prepared by not adding modified titanium dioxide and adding unmodified nano titanium dioxide in Comparative Examples 10 and 11 is significantly increased compared with Examples 54-62. Due to the large specific surface area of nano titanium dioxide, it can adsorb polymer molecular chains to form physical crosslinking points. At the same time, the modification treatment of the silane coupling agent improves the compatibility of nano titanium dioxide and polystyrene. When the plastic is subjected to stress, the stress can be transferred to other molecular chains through crosslinked particles, so that the stress distribution is uniform, and the friction stress in the local area is reduced. At the same time, the thermal conductivity of the inorganic particles is better than that of polystyrene. The molecular chain can form an effective heat-conducting network chain in the matrix to transfer the heat generated inside the matrix, which is beneficial to reduce material wear; in comparative example 12, no lubricant calcium carbonate is added. Compared with Example 54, the volume wear amount is increased to a certain extent. By compounding two calcium carbonates with different particle sizes, when pitting occurs on the plastic surface during the wear process, calcium carbonates with different particle sizes can be filled in time to remedy the pitting sites and avoid damage to the SMT carrier due to friction and wear during repeated use; the results of Examples 54-56 show that the silanol formed after the hydrolysis of the silicon-oxygen bond of KH-570 can combine with the hydroxyl group on the surface of nano-titanium dioxide, and the exposed olefin bonds can improve The silanol ends have good compatibility with the whole of polystyrene, and at the same time, the excess silanol ends undergo condensation reactions with other molecules in all directions to form a Si-O-Si three-dimensional network on the surface of the nano-titanium dioxide particles, further improving the mechanical properties of the polystyrene plastic. The results of Examples 54 and 57-59 show that with the increase in the amount of silane coupling agent used, the volume wear of the polystyrene plastic shows a trend of gradually decreasing. However, the addition of excessive silane coupling agent greatly accelerates the self-condensation reaction rate between silanol molecules, inhibits the condensation reaction between silanol and Si-OH on the surface of nano-titanium dioxide, and increases the possibility of agglomeration of inorganic particles, further Reduce the compatibility of plastics and reduce the mechanical properties of plastics; the results of Examples 54 and 60-62 show that with the increase in the amount of modified titanium dioxide, the volume wear of the plastic shows a trend of first decreasing and then increasing. Excessive titanium dioxide will cause the inorganic particles in the plastic system to agglomerate, further affecting the mechanical properties. At the same time, the cross-linking points formed by the agglomerated inorganic particles and the polystyrene plastic are reduced, and the dispersion of friction stress is reduced, resulting in an increase in volume wear; It can be seen from the results of Table 7 that using KH-570 as a silane coupling agent and controlling the amount of modified titanium dioxide, the volume wear of the obtained polystyrene plastic is 0.82 mm 3 , showing significantly improved wear resistance.
[0107] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing polystyrene plastic for SMT carrier tape, characterized in that: The preparation of the polystyrene plastic comprises the following steps: 40-80 parts of modified polystyrene, 20-60 parts of modified polycarbonate and 10-25 parts of modified inorganic particles are vacuum dried to obtain a dried material; the dried material is added into a continuous mixer, 5-15 parts of a toughening agent, 3 parts of a lubricant and 5 parts of an antioxidant are added under stirring conditions, the temperature is raised to 220° C., and the mixture is stirred and mixed for 30 minutes to obtain a rubber compound; the rubber compound is melt-extruded in a twin-screw extruder, plasticized and granulated to obtain the polystyrene plastic; Polymerizing polystyrene with terminal olefinic polysiloxane to obtain a polystyrene precursor; and subjecting the polystyrene precursor to heat treatment to obtain the modified polystyrene; The modified polycarbonate is prepared by subjecting diphenyl carbonate, bisphenol A and an antioxidant to transesterification under the action of sodium hydroxide and condensation polymerization; Modifying the inorganic particles with a silane coupling agent at 60° C. to obtain the modified inorganic particles; The lubricant is selected from calcium carbonate complex; the antioxidant is selected from antioxidant 1010.
2. The method for preparing a polystyrene plastic for SMT carrier tape according to claim 1, characterized in that: The preparation of the modified polystyrene precursor comprises the following steps: Add terminal hydroxyl polysiloxane and tert-butylhydroquinone into a flask, dissolve in dichloromethane, and stir to obtain a mixed solution; add acryloyl chloride and triethylamine to the mixed solution, heat to 40°C, and react for 3 hours to obtain the terminal olefin polysiloxane; add dibutyltin dilaurate to the terminal olefin polysiloxane, stir to react, and obtain a reaction solution; add the polystyrene to the reaction solution, and react at 80°C for 1 hour to obtain a reaction system; cool the reaction system, rotary evaporate, and dry to obtain the modified polystyrene precursor; wherein the mass ratio of the polystyrene to the terminal olefin polysiloxane is 1:5-15.
3. The method for preparing a polystyrene plastic for SMT carrier tape according to claim 1, characterized in that: The preparation of the modified polystyrene comprises the following steps: The modified polystyrene precursor is added into a reaction kettle, the temperature is raised to 100-200°C, and the temperature is kept for 30-90 minutes to obtain a melt; the melt is cooled at a cooling rate of 5-20°C / min to obtain a cooled product; the cooled product is rinsed and dried to obtain the modified polystyrene.
4. The method for preparing a polystyrene plastic for SMT carrier tape according to claim 1, characterized in that: The toughening agent is selected from one of polybutylene terephthalate, acrylonitrile-butadiene-styrene copolymer, styrene-butadiene-styrene block copolymer and ethylene-vinyl acetate copolymer.
5. The method for preparing polystyrene plastic for SMT carrier tape according to claim 1, characterized in that: The preparation of the modified polycarbonate comprises the following steps: The diphenyl carbonate, the bisphenol A and the antioxidant are added into a reaction bottle, and the sodium hydroxide is added, and an ester exchange reaction is carried out at 200° C. for 1 hour under a nitrogen atmosphere to obtain a mixed system; the vacuum pressure of the mixed system is adjusted to 30 KPa, the temperature is raised to 250° C., and the reaction is carried out for 30 minutes to obtain a product one; the pressure of the product one is reduced to 5 KPa, the temperature is raised to 280° C., and the reaction is carried out for 30 minutes to obtain a polymer; the polymer is dissolved in dichloromethane, and methanol is added to precipitate a precipitate; the precipitate is separated and centrifuged, rinsed with methanol, and vacuum dried at 80° C. for 2 hours to obtain the modified polycarbonate.
6. The method for preparing polystyrene plastic for SMT carrier tape according to claim 5, characterized in that: The mass ratio of the diphenyl carbonate, the bisphenol A and the antioxidant is 10-30:15-45:1; the antioxidant is 2-(2,4-dihydroxyphenyl)-4,6-bis(2,4-xylyl)-1,3,5-triazine.
7. The method for preparing polystyrene plastic for SMT carrier tape according to claim 1, characterized in that: The preparation of the modified inorganic particles comprises the following steps: The inorganic particles are added to anhydrous ethanol, and ultrasonically oscillated for 30 minutes to obtain a suspension; the silane coupling agent is added to anhydrous ethanol, and stirred for 30 minutes to obtain a modifier solution; the modifier solution is added to the suspension, magnetically stirred, and subjected to a modification reaction at 60° C. for 2 hours to obtain the modified inorganic particles.
8. The method for preparing polystyrene plastic for SMT carrier tape according to claim 7, characterized in that: The inorganic particles are selected from one of nano titanium dioxide, nano silicon dioxide, nano graphene and nano calcium carbonate.
9. The method for preparing polystyrene plastic for SMT carrier tape according to claim 7, characterized in that: The silane coupling agent is selected from one of methylvinyl dimethoxysilane, vinyl triisopropoxysilane and methacryloxypropyl trimethoxysilane; the mass ratio of the inorganic particles to the silane coupling agent is 3-10:
1.
10. The polystyrene plastic for SMT carrier tape prepared by the method of claim 1, characterized in that: The polystyrene plastic comprises modified polystyrene, modified polycarbonate, modified inorganic particles, a toughening agent, a calcium carbonate compound and an antioxidant 1010.
Citation Information
Patent Citations
Antistatic plastic for SMT carrier band, and preparation and use thereof
CN101475721B
Cited By
Anti-yellowing and anti-aging silicone sealant and preparation method thereof
CN119081640A